SOSIALISASI FIKIH MUAMALAT PRAKTIS DALAM KEHIDUPAN SEHARI-HARI: PENCEGAHAN JERATAN PINJOL DAN RIBA DI MASJID NURUL HILAL CENGKARENG - Hidayat (LPPM STAI Muhammadiyah Probolinggo, 2022)
Cengkareng District, West Jakarta, as one of the most densely populated areas in DKI Jakarta, faces complex socio-economic challenges in the second decade of the 21st century. Modern financial phenomena, marked by the aggressive penetration of Financial Technology (Fintech), specifically Peer-to-Peer Lending (Pinjol) and Paylater features, have created new vulnerabilities among low and middle-income communities. Based on data from the 2019 National Survey of Financial Literacy and Inclusion (SNLIK) by the Financial Services Authority (OJK), there is a concerning gap between the national financial inclusion index reaching 76.19% and the sharia financial literacy index which remains stagnant at 8.93%. This disparity creates a void where the community accesses financial products without adequate understanding of risks and sharia compliance, resulting in widespread